IDF Diabetes Atlas estimates of 2014 global health expenditures on diabetes. (July 2016) - da Rocha Fernandes, Joao; Ogurtsova, Katherine; Linnenkamp, Ute; Guariguata, Leonor; Seuring, Till; Zhang, Ping; Cavan, David; Makaroff, Lydia E.
Highlights: Global diabetes-related health expenditures were estimated for 2014. At least USD 612 billion (ID 673 billion) were spent globally on diabetes. The mean health expenditure per person with diabetes was at least USD 1583 (ID 1742). The North America and Caribbean Region spent more than all other regions combined. Abstract: Aims: To estimate health expenditures due to diabetes in 2014 for the world and its regions. Methods: Diabetes-attributable health expenditures were estimated using an attributable fraction method. Data were sourced from International Diabetes Federation (IDF) estimates of diabetes prevalence, UN population projections, WHO annual health expenditure reports, and estimates of the cost ratio of people with and without diabetes. Health expenditures were calculated in both US dollars (USD) and international dollars (ID). Results: The average health expenditure per person with diabetes worldwide in 2014 was estimated to range from USD 1583 (ID 1742) to USD 2842 (ID 3110). The estimated annual global health expenditure attributable to diabetes ranged from USD 612 billion (ID 673 billion) to USD 1099 billion (ID 1202 billion). Together, the North America and Caribbean Region and the Europe Region were responsible for over 69% of the costs, and less than 10% of the costs were from the Africa Region, South East Asia Region, and Middle East and North Africa Region combined. The North America and Caribbean Region had the highest annual spending per person with diabetes (USD 7984 [ID 8040.39]), while the South East Asia Region had the lowest annual spending per person with diabetes (USD 92 [ID 234]). Conclusions: Diabetes imposes a large economic burden on health care systems across the world, yet varies across world regions. Diabetes prevention and effective management of diabetes should be a public health priority to reduce the financial burden.